Substance use disorders in a wartime context: clinical features, neurobiological mechanisms, and rehabilitation approaches - Kadyrov, Asan (Psychosomatic Medicine and General Practice, 2026)
Background. War represents a powerful multifactorial driver of mental disorders, combining acute trauma with chronic stress exposure. In this context, substance use disorders (SUDs) gain particular clinical relevance as maladaptive coping strategies and are frequently comorbid with post-traumatic stress disorder (PTSD), depression, and anxiety disorders. Objective. To analyze the clinical and psychopathological features, neurobiological mechanisms, and psychosocial determinants of substance use disorders in a wartime context, and to identify current approaches to their diagnosis and rehabilitation. Materials and methods. This study was conducted as a narrative literature review. Scientific publications indexed in PubMed, Scopus, and Web of Science, as well as reports from international organizations and national analytical sources published between 2000 and 2025, were analyzed. Methods included research analysis, comparative literature analysis, and conceptual synthesis. Results. Wartime conditions contribute to the formation of specific patterns of addictive behavior driven by the interaction of traumatic exposure, chronic stress, and limited access to adaptive coping strategies. Neurobiological mechanisms play a key role, including dysregulation of the hypothalamic-pituitary-adrenal axis, alterations in cortico-limbic networks, and dysfunction of the dopaminergic reward system. High comorbidity with PTSD, depression, and anxiety disorders is associated with more severe clinical courses, rapid progression, and increased treatment complexity. Stimulant use disorders and polysubstance use represent particularly severe clinical patterns. Conclusions. Substance use disorders in wartime represent a complex biopsychosocial phenomenon requiring integrated, trauma-informed, and personalized approaches to diagnosis and treatment. Effective rehabilitation should focus not only on substance use reduction but also on restoring psychosocial functioning, quality of life, and life meaning. Keywords: mental disorders, behavioral disorders, psychoactive substances, addictive disorders, war, stimulants, post-traumatic stress disorder, comorbidity, neurobiology, rehabilitation. УДК 616.89-008.441.13:355.01